The Implementation of Quizizz as Digital Game Based Media Toward the Students' Reading Comprehension at SMK Telkom Makassar - Rosmawati; Amirullah; Sahril (International Journal of Language, Education, and Literature, 2024)
It is impossible to separate the development of education from technological advancements. Alongside these developments, using technology-based media has transformed the teaching and learning process. In this study, the researcher investigated the application of Quizizz, which is a game-based learning application. This focuses more on the implementation, perception, and impact of Quizizz on students' reading comprehension at SMK Telkom Makassar. Therefore, this research aimed to determine how the implementation, effectiveness, and student's perceptions of Quizizz as a digital game-based medium affect students' reading comprehension. This study used a qualitative method, with observation, interviews, and documentation as instruments. The research findings demonstrated that the implementation of Quizizz was user-friendly, resulting in students experiencing enjoyment, comfort, and motivation during the teaching-learning process. Additionally, Quizizz enhanced student engagement by fostering an interactive classroom environment where students actively participate in teaching-learning activities. As a result, Quizizz has a simple implementation, a positive perception, and a significant impact.